2020
DOI: 10.1002/ajmg.a.61785
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal genetic diagnosis of cranioectodermal dysplasia in a Polish family with compound heterozygous variants in WDR35

Abstract: The ciliary chondrodysplasias represent a group of clinically and genetically heterogeneous disorders that affect skeleton development. Cilia are organelles that project from the surface of many cell types and play an important role during prenatal and postnatal human development. Cranioectodermal dysplasia (Sensenbrenner syndrome, CED) is a ciliopathy primarily characterized by craniofacial, skeletal, and ectodermal abnormalities. To date six genes have been associated with CED: IFT122, WDR35, WDR19, IFT140, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…In addition, a polydactyly, which is not a frequent feature of CED (Lin et al, 2013) was only reported in Patient 5 and cutaneous syndactyly of 2/3 toes was present in Patients 1, 2, and 4. This feature was previously reported in five affected individuals from four other CED families with pathogenic variants in WDR35 (Gilissen et al, 2010;Bacino et al, 2012;Walczak-Sztulpa et al, 2018;Walczak-Sztulpa et al, 2020).…”
Section: Segregation Analysissupporting
confidence: 79%
See 4 more Smart Citations
“…In addition, a polydactyly, which is not a frequent feature of CED (Lin et al, 2013) was only reported in Patient 5 and cutaneous syndactyly of 2/3 toes was present in Patients 1, 2, and 4. This feature was previously reported in five affected individuals from four other CED families with pathogenic variants in WDR35 (Gilissen et al, 2010;Bacino et al, 2012;Walczak-Sztulpa et al, 2018;Walczak-Sztulpa et al, 2020).…”
Section: Segregation Analysissupporting
confidence: 79%
“…Our study is unique as all of these CED patients have identical likely pathogenic compound heterozygous WDR35 variants: c.1922T>G encoding p.(Leu641Ter) and c.2522A>T encoding p.(Asp841Val). Notably, both variants have previously been reported as causal variants in CED; p.(Leu641Ter) has been reported as a causal variant in at least two unrelated patients with CED (Hoffer et al, 2013; Li et al, 2015) and p.(Asp841Val) in two other unrelated CED families (Walczak‐Sztulpa et al, 2018; Walczak‐Sztulpa et al, 2020). In other words there are four Polish CED families reported with a heterozygous p.(Leu641Ter) variant and six families with a heterozygous p.(Asp841Val) amino acid substitution, which leads us to believe that both changes are founder variants in the Polish population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations